Sex, Drugs, and Suicide in Youth-oriented TV Series of Different Countries: Controversial Content and the Level of Acceptability for a Sensitive Audience - Rosinska, Olena (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
This article investigates the portrayals of acute problems faced by young people, a sensitive population category, in youth-oriented series available on various open media platforms, both international (such as Netflix, YouTube) and national ones (for example, Polsat Box Go, TVP, Megogo, Volia, Oll. tv, etc.). Additionally, the study aims to examine the censorship methods employed by national media platforms for media content targeting a highly sensitive youth audience. The research focuses on TV series for youth and adolescents as a specific genre of artistic and educational content that addresses significant personal and social issues while entertaining. This includes the Polish series Sexify (2021, 2022); the Ukrainian series First Swallows (2019, 2020), Sex, Insta and ZNO (2020), the Spanish web series Elite (2018); the British series Sex Education (2019); and the American series 13 Reasons Why (2017–2020), all of which are intended for viewers aged 16 and over. The Ukrainian series of The New One (2019) is not subject to detailed analysis but is mentioned for comparison and as an example available on the Netflix platform. The research addresses such issues as differing perceptions of youth-oriented series by representatives of different generations and the provision of certain behaviour models through media content.